Understanding project cost contingency: A survey - Baccarini, David (Queensland University of Technology, 2005)
Patrascu (1988) observed nearly two decades ago that "contingency is probably the most misunderstood, misinterpreted, and misapplied word in project execution." Since that time there has been little empirical research into project people’s understanding of the concept of project cost contingency. This paper reports the results of a survey of 78 project practitioners’ comprehension of issues pertaining to project cost contingency. Whilst there is consensus that cost contingency is a reserve of money which should be used for scope changes, a key finding is that there is a lack of appreciation that project cost contingency is a risk management notion. Consequently, the majority of practitioners (77%) continue to use a deterministic percentage approach for estimating project cost contingency. Furthermore, 46% of respondents work in organisations that do not have a policy on contingency and 36% do not manage the use of contingency. Overall, this suggests there is significant room for improvement in the understanding, estimation and management of project cost contingency.